THE CONCEPT OF INSĀN RABBĀNĪ IN IBN ‘ARABĪ’S THOUGHT: A SEMIOTIC ANALYSIS THROUGH CHARLES S. PEIRCE’S FRAMEWORK - Muhammad Nasiruddin; Helmi Syaifuddin; Ahmad Kholil (UIN Raden Mas Said Surakarta, 2024)
Humans were created with a perfect soul, mind and intellect. But he often forgets the purpose of his creation. As a mirror of the Divine, humans can achieve Divine self-awareness, as the Prophet Muhammad said, ‘Whoever knows himself will know his Lord.’ According to Ibn ‘Arabī, humans who know their God are called insān kāmil, and insān kāmil recognised by God is called insān rabbānī. This article examines the steps and ways towards insān rabbānī according to Ibn ‘Arabī, and analyses the symbols and their meanings based on Charles S. Pierce's semiotic theory. The analysis is descriptive-explanatory based on content analysis. Initially, semiotic was only used in the empirical realm. It becomes interesting when semiotics is applied to the metaphysical realm; an attempt to think logically, philosophically, reflectively, and contextually in looking at Sufism in Indonesia. This article shows that the steps and ways to reach insān rabbānī; such as taubah, murāqabah, and ikhlāṣ, to reach waḥdah al-wujūd and musyāhadah. The symbol of insān rabbānī is depicted through the concept of waḥdah al-wujūd in a triadic process; that humans are the manifestation of God, the form of insān rabbānī is manifested in Rasūl, Prophet, Walī, and Waraṡah al-Anbiyā’, who act as caliphs of Allāh. With God’s adab and authority, insān rabbānī guides humans towards Divine self-awareness.